Sex determination in fish - Pandian. T. J. (Science Publishers, 2011)
"As the book is a continuum of the earlier book 'Sexuality in Fishes', there are a few unavoidable but obligatorily required duplications to keep each chapter complete and independent, besides pointing out areas of research requiring critical inputs. None of the earlier reviews/books have ever considered allogenics/xenogenics; this book is the first to report that research in this frontier area have conclusively shown that fishes have retained bisexual potency even after sexual maturity and spermiation. The XY genotype found in the unexpected female phenotypes sired by supermales (Y1Y2) and androgenic males (Y2Y2) points out the need to employ sex specific molecular markers to identify the true genotype of a juvenile, which matures either as a male or female, depending upon the sex of its pair (female or male) and thereby critically assessing the environmental role in sex determination. This book is meant to assist molecular biologists in the search of sex determining gene(s), fishery biologists endeavouring to develop techniques for profitable monosex aquaculture and ecologists interested in conservation of fishes and their genomes."--Provided by publisher.